Cross-Cultural Adaptation of the Kidscreen Questionnaire to Measure Health-Related Quality of Life in the 8 to18 Year-Old Mexican Population [Adaptación Transcultural del Cuestionario Kidscreen Para Medir Calidad de Vida Relacionada Con la Salud en Población Mexicana de 8 a 18 Años] - Montano-Espinoza, R (Associacao Brasileira de Pos - Graduacao em Saude Coletiva, 2014)
The scope of this study was to develop the culturally-adapted version of the KIDSCREEN- 52 questionnaire for Mexican adolescents aged 8 to 18, and to analyze its reliability and validity. A translation and back translation was carried out from English to Spanish and vice versa. Cognitive interviews were conducted and confirmatory factor analysis (CFA) was used to verify the content validity of the questionnaire. Based on previous studies (i.e. the Argentinian version) mean scores of dimensions were compared to assess construct validity. Reliability was also analyzed. The results showed that the content validity of the version retained the original concepts, duly adapted to the Mexican culture and language. The AFC confirmed the structure of the 10 original dimensions. Two scales achieved the ceiling effect. The instrument s internal consistency was acceptable (ranged from 0.5 to 0.86), and reproducibility obtained low coefficients in 5 dimensions (0.22 to 0.78). The Mexican KIDSCREEN- 52 version is equivalent to the original in terms of content, structure, and construct validity. The conclusion was that the KIDSCREEN- 52 tool is suitable for application in the Mexican population aged 8 to 18. Further studies are needed to explore its application in clinical settings.